Sexist Socialization Experienced by Female Protagonists in Anthology Short Story Translated by Dayla - Munawwaroh, Ulfatul; Suryani, Suci (Vivid: Journal of Language and Literature, 2022)
Sexism over women is deeply entrenched in society. It becomes a worldwide issue evinced by multiplicity of literary works narrating discriminations of society against women where women's position is often exploited, humiliated, and even cornered. This article is designed to analyze the sexist oppressions experienced by female protagonists in Anthology Short Stozy Arab Women Writer translated by Dayla Cohen-Mor, the sexist socializations in the short stories as well as their responses towards the sexism. In analyzing this data, the writers scrutinize ten short stories selected and apply feminist theory: from margin to center by bell hooks (1984). The result imparts that sexism is socialized through behaviour andculture in society.